Analisis Yuridis Tindak Pidana Pendanaan Terorisme Melalui Yayasan Amal (Studi Kasus Putusan Pengadilan Negeri Jakarta Timur Nomor 278/Pid.Sus/2022/PN Jkt.Tim) - Nanda, Nanda; Cumbhadrika, Chitto (PT Elaborium Elevasi Indonesia, 2025)
Terrorism Financing is any action in the context of providing, collecting, giving or lending funds, either directly or indirectly, with the intention of being used and/or known to be used to carry out terrorist activities, terrorist organizations or terrorists. Finance or Funding is an important part of a terrorist attack, funds are very important in acts of terrorism because they will be used to support all actions that will be carried out to facilitate acts of terrorism, such as introducing ideology, funding the needs of terrorist members and their families, funding travel and housing, and recruitment , train new terrorists, obtain new names and documents, purchase weapons, and plan and carry out activities. The problem in this research is how are the qualifications for the criminal act of financing terrorism through charity foundations and also how is the application of criminal law and the judge's consideration of the criminal act of financing terrorism through charity foundations in Court Decision Number: 278/Pid.Sus/2022/PN Jkt.Tim. The research method used is normative juridical research using library data such as statutory regulations, court decisions, books etc. The research results show that the qualifications for criminal acts of financing terrorism through charitable foundations are contained in Article 4 of Law no. 9 of 2013 concerning Prevention and Eradication of Terrorism Financing Crimes. The application of criminal law to criminal acts of financing terrorism through charitable foundations, namely imprisonment and fines. The judge's considerations in court decision Number:278/Pid.Sus/2022/PN Jkt.Tim still does not fulfill the sense of justice because the sentence period proposed by the prosecutor and decided by the judge is still considered insufficient and not appropriate.